APPLICATION AND VALIDATION OF DERIVATIVE SPECTROPHOTOMETRIC FOR DETERMINATION LEVELS OF TERNARY MIXTURES OF PARACETAMOL, PROPYPHENAZONE, AND CAFFEINE IN TABLET DOSAGE FORM - Sianipar, Artha Yuliana; Muchlisyam, Muchlisyam; Morin Sinaga, Siti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study was to develop a spectrophotometric method with derivative zero-crossing for determines the levels of paracetamol (PCT), propyphenazone (PRO), and caffeine (CAF) in tablet dosage form without prior separation. Method: The study begins with optimizing the type of solvent, phosphate buffer (pH 7.2) and a mixture of phosphate buffer (pH 7.2) with methanol at ratio 90:10; 70:30; 50:50; 30:70; and 10:90. Spectrophotometric method with zero-crossing, tested validity based on linearity, accuracy, precision, limit of detection, and limit of quantification. Then, the method applied to determine the levels of PCT, PRO, and CAF in tablet. Result: The mixture of phosphate buffer (pH 7.2) with methanol at ratio 70:30 can be used for analysis. Applications zero-crossing technique on assay of PCT and CAF performed on the first derivative and Î”Î» 2 with Î» 239.4 nm for PCT and Î”Î» 8 with Î» 245.6 nm for CAF while PRO in the third derivative and Î”Î» 8 with Î» 249.6 nm, resulting 100.91%, 104.75%, and 103.33% for levels of PCT, PRO, and CAF, respectively. Conclusion: Spectrophotometric derivative method with zero-crossing qualified in validation parameters.